2018
DOI: 10.1016/j.prnil.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Prostate irradiation with focal dose escalation to the intraprostatic dominant nodule: a systematic review

Abstract: Radiation therapy (RT) is a curative treatment option for localized prostate cancer. Prostate irradiation with focal dose escalation to the intraprostatic dominant nodule (IDN) is an emerging treatment option that involves the prophylactic irradiation of the whole prostate while increasing RT doses to the visible prostatic tumor. Because of the lack of large multicentre trials, a systematic review was performed in an attempt to get an overview on the feasibility and efficacy of focal dose escalation to the IDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 79 publications
(176 reference statements)
5
49
1
2
Order By: Relevance
“…7 Despite the strong level-1 scientific evidence supporting the use of ADT with conventional EBRT in intermediate-and high-risk patients, a recent systemic review reported that only 27.8% of the patients treated in the context of prostate dose escalation received ADT. 48 According to the current evidence, it is difficult to rule out that dose escalation to the DIN could provide a benefit for local tumor control in the same magnitude as the addition of ADT. Certainly the lack of use of ADT in our study limits generalizability of our results because according to the standard approach, these patients should have all received ADT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…7 Despite the strong level-1 scientific evidence supporting the use of ADT with conventional EBRT in intermediate-and high-risk patients, a recent systemic review reported that only 27.8% of the patients treated in the context of prostate dose escalation received ADT. 48 According to the current evidence, it is difficult to rule out that dose escalation to the DIN could provide a benefit for local tumor control in the same magnitude as the addition of ADT. Certainly the lack of use of ADT in our study limits generalizability of our results because according to the standard approach, these patients should have all received ADT.…”
Section: Discussionmentioning
confidence: 98%
“…Mature prostate SBRT trials have been summarized in a recent review. 48 7 Katz reported 10-year biochemical control of 93% for low-risk patients who received 35 to 36.25 Gy in 5 daily fractions. 49 A Canadian trial recently reported 5-year biochemical control rate of 97% in patients at low-to intermediate risk who were treated with 40 Gy in 5 fractions delivered over 29 days (once-a-week treatment).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 2036 prostate SABR patients showed pooled late grade 3+ GU and GI toxicity to be 2% and 1% respectively [23] . Studies incorporating a DIL boost report slightly higher grade 3+ toxicity; between 2 and 6% for IMRT and brachytherapy boost techniques, and up to 10% for SABR boosts [8] but long term follow up is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support dose escalation to the DIL is increasing, with the hypo-FLAME trial recently reporting favourable results [22] . A recent systematic review identified 22 trials of prostate radiation therapy with focal dose escalation to the intraprostatic dominant nodule [8] , a term used interchangeably with DIL. Biochemical control was achieved in 80–100% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation